Evaluation of factors affecting survival rate in primary bone sarcomas with extremity and pelvis involvement - EROL, BÜLENT (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2020)
Objective: This study is an evaluation of the overall survival rate and factors affecting survival in patients with osteosarcoma, chondrosarcoma, or Ewing's sarcoma. 'This study aimed to determine the effect of factors related to the preoperative period, patient, tumor, treatment, and postoperative period on survival. Methods: A total of 114 patients (64 male and 50 female) with osteosarcoma, chondrosarcoma, or Ewing's sarcoma treated between 2005 and 2013 were included in this study. All the patients received standard treatment and were followed up regularly. In all, 44 cases of (conventional and telangiectatic) osteosarcoma, 30 cases of Ewing's sarcoma, and 40 cases of high-grade chondrosarcoma were identified using the Bone and Soft Tissue Tumor Registry. Gender, age, tumor size and localization, pathological fractures, histopathological type, grade, surgical treatment, adjuvant treatments, relapse of the disease, and postoperative complication data were obtained from follow-up forms. The learning curve of institutional expertise was also evaluated. The patient survival rate was calculated using the Kaplan-Meier method, and log-rank statistical methods were used to compare survival rates. Results: The mean length of survival of the patients was 72 months. There was a 56% 5-year survival rate, and the event-free survival rate was 53%. The survival of patients with Ewing's sarcoma whose prodromal period was less than 12 weeks was significantly higher than that of the other groups (p=0.031). The survival of patients with tumor size greater than 150 cc, with local recurrence and distant metastases was low for all groups. Survival rates were significantly lower in osteosarcoma and Ewing's sarcoma patients with stage III tumor or metastasis at diagnosis. The survival of patients with osteosarcoma diagnosed between 2010 and 2013 was significantly higher than that of the earlier group (p=0.02). Conclusion: Decreasing the prodromal period (early diagnosis) can improve survival by preventing the local and systemic spread of the tumor. Increase in the surgical experience is likely to have a positive effect on survival rates, especially for patients with osteosarcoma. The relapse of the disease is a poor prognostic factor for survival despite aggressive surgery and adjuvant therapies.
Keywords: Early diagnosis; Overall survival; Primary bone sarcomas; Survival; Learning curve; HIGH-GRADE OSTEOSARCOMA; PROGNOSTIC-FACTORS; EWINGS-SARCOMA; LOCAL RECURRENCE; POSTOPERATIVE INFECTION; CHONDROSARCOMA; CHEMOTHERAPY; EXPERIENCE; FINLAND; DISEASE